Do metallic-coated cups affect the perception of specialty coffees? An exploratory study - Carvalho, F; Spence, C (Elsevier, 2020)
The presence of a metallic surface or appearance of product packaging and servingware can impact both the sensory and hedonic perception of various different foods and beverages, including promoting the impression of quality, premiumness, and luxury. A total of 51 coffee experts and 132 consumers took part in the study. Metallic-coated ceramic cups were used to assess whether the outer coating of the cup would influence the perception of two distinct coffee profiles. Hedonic and sensory ratings were assessed. Given the known link between visual metallic surfaces and premium/luxury perception, we also assessed whether participants' impressions of elegance might be mediating between the cup and positive sensory and hedonic judgments. Interaction effects between coffee type and cup finish revealed that higher sensory and hedonic ratings were given to the Brazilian coffee when it was tasted from the bronze cup, and to the Kenyan coffee when sampled from the gold cup (as compared to all other cups). Interaction effects including ‘expertise level’ showed that experts (in contrast to consumers) gave higher ratings of sweetness for both Brazilian and Kenyan when tasted from the bronze cup. Moreover, ‘elegance’ was a predictor of positive judgments when the Brazilian coffee was served in the bronze cup (for both experts and consumers) and when the Kenyan coffee was served in the white cup (for experts only). Despite the preliminary nature of these results, they nevertheless merit consideration by the industry. In addition to innovation, it makes sense to create receptacles that convey some functional and/or perceptual benefit to the coffee drinking experience.